2009
DOI: 10.2527/jas.2008-1068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen-protected methionine supplementation and bacterial lipopolysaccharide infusion on nitrogen metabolism and hormonal responses of growing beef steers1

Abstract: Metabolic demand for sulfur-containing AA increases during inflammation in nonruminants. Therefore, Met supplementation may alleviate the negative effects of infection on N balance. Effects of gram-negative bacterial lipopolysaccharide (LPS) and supplemental dietary Met on N balance, serum hormones and haptoglobin, and plasma urea-N and AA were evaluated in 20 Angus-cross steers (BW = 262 +/- 6.3 kg). Treatments (2 x 2 factorial) were infusion of no LPS (-LPS) or a prolonged low dose of LPS (+LPS) and dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 48 publications
(52 reference statements)
8
17
1
Order By: Relevance
“…The decreased plasma concentrations observed for most essential and non-essential AA in response to LPS are similar, but not identical, to changes observed previously in steers (26) and foals (27) as well as in pigs with respiratory disease (28) . Under the conditions of endotoxaemia within the current ovine model, although the majority of AA (except leucine and tyrosine) showed altered plasma concentrations when LPS was infused, nine of these did not show a differential response compared with saline during the AA infusion (which can be taken as a surrogate for a protein source of similar AA composition).…”
Section: Discussionsupporting
confidence: 86%
“…The decreased plasma concentrations observed for most essential and non-essential AA in response to LPS are similar, but not identical, to changes observed previously in steers (26) and foals (27) as well as in pigs with respiratory disease (28) . Under the conditions of endotoxaemia within the current ovine model, although the majority of AA (except leucine and tyrosine) showed altered plasma concentrations when LPS was infused, nine of these did not show a differential response compared with saline during the AA infusion (which can be taken as a surrogate for a protein source of similar AA composition).…”
Section: Discussionsupporting
confidence: 86%
“…McMahon et al (1999) observed an increase in BUN concentrations 12 and 24 h following LPS administration in dairy steers at concen-trations similar to those reported in the current study. Waggoner et al (2009a) also reported similar increases in BUN concentrations measured in Anguscross steers administered LPS compared with steers administered saline.…”
Section: Discussionsupporting
confidence: 59%
“…Waggoner et al. () also reported similar increases in BUN concentrations measured in Angus‐cross steers administered LPS compared with steers administered saline.…”
Section: Discussionmentioning
confidence: 62%
“…Waggoner et al (2009) experimentally challenged beef steers with endotoxin, and plasma concentrations of isoleucine and leucine decreased 4 h post-infusion with LPS when compared with unchallenged controls (Waggoner et al, 2009). Similarly, clearance kinetics in human subjects intravenously perfused with AA indicated greater removal of several AA in patients with microbial sepsis when compared with healthy controls, presumably as a result of hepatic extraction (Dmml et al, 2001).…”
Section: Hepatic Protein Metabolismmentioning
confidence: 91%